Strategi Pemerintah Kota Cilegon Dalam Meningkatkan Pendapatan Asli Daerah (PAD) Melalui Rencana Pengembangan Situ Rawa Arum Sebagai Destinasi Wisata di Kota Cilegon - Devi Junia Fitri (Faculty of Social, Politic, and Law Science, Universitas Serang Raya, 2023)
The Cilegon City Government has a vision and mission in advancing the region, one of which is by developing and optimizing the tourism sector in Cilegon City. The aim of developing Tirta Situ Rawa Arum Tourism is as a tourist destination in Cilegon City which is able to increase local revenue (PAD), the economy of local residents and increase MSMEs. The purpose of this study was to analyze the government's strategy in the construction and development of tourism objects in Situ Rawa Arum Tourism in Cilegon City. This research method uses descriptive qualitative research and a normative juridical approach, data collection and documents obtained by observation, interviews and documentation techniques. The results of the study show that the Cilegon City government's strategic policies in increasing PAD from the tourism sector are still not optimally managed. So that the Cilegon City government has the strategy to make Situ Rawa Arum a tourist destination by increasing the number of tourist visits, the quality of the bureaucracy and the quality of public services as well as the development of facilities and infrastructure in the area.